2015
DOI: 10.1016/j.jacc.2014.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Should Atrial Fibrillation Patients With 1 Additional Risk Factor of the CHA2DS2-VASc Score (Beyond Sex) Receive Oral Anticoagulation?

Abstract: Not all risk factors in CHA2DS2-VASc score carry an equal risk, with age 65 to 74 years associated with the highest stroke rate. Oral anticoagulation should be considered for AF patients with 1 additional stroke risk factor given their high risk of ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
169
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(185 citation statements)
references
References 36 publications
5
169
0
11
Order By: Relevance
“…The study protocol of the present study was similar to those of our previous studies 5, 6, 7, 8, 9, 10, 11. From January 1, 2000 to December 31, 2011, a total of 289 559 AF patients aged ≥20 years (10 336 with liver cirrhosis) were identified from the NHIRD.…”
Section: Methodsmentioning
confidence: 91%
“…The study protocol of the present study was similar to those of our previous studies 5, 6, 7, 8, 9, 10, 11. From January 1, 2000 to December 31, 2011, a total of 289 559 AF patients aged ≥20 years (10 336 with liver cirrhosis) were identified from the NHIRD.…”
Section: Methodsmentioning
confidence: 91%
“…In contrast, the European guidelines recommend oral anticoagulants among patients with ≥1 stroke risk factors 19. Estimates of baseline untreated stroke risk in this low‐risk population vary in the literature 13, 46, 47. We found that adherence to anticoagulation was not associated with a significant reduction in stroke in patients with CHA 2 DS 2 ‐VASc score 0 or 1, suggesting that the stroke risk is not easily modified in low‐risk patients and that the bleeding risk is nontrivial.…”
Section: Discussionmentioning
confidence: 99%
“…Lip and colleagues in a large Danish cohort of patients with AF demonstrated that in untreated patients with 1 additional stroke risk factor (CHA 2 DS 2 VASc=1 [male],=2 [female]), strokes rates increased 3‐fold compared with untreated low‐risk patients (CHA 2 DS 2 VASc=0 [male], =1 [female]) 20. Similarly, Chao and colleagues in a large Taiwanese cohort of patients with AF demonstrated that untreated patients with 1 additional risk factor for stroke derived a benefit from OAC given their increased risk of ischemic stroke 21. Conversely, Friberg and colleagues, in a large Swedish cohort, showed that untreated patients with 1 additional stroke risk factor had lower risk of ischemic stroke than previously reported and that the use of OAC in this group provided no associated benefit 18…”
Section: Discussionmentioning
confidence: 99%